RUU MINOL DAN KRITIK ELITISME: TELAAH LIRIK LAGU DAN MUSIK VIDEO ORANG MISKIN DILARANG MABOK - Nuzurul Rochmah; Guntur Sekti Wijaya; Haris Shofiyuddin (Universitas Negeri Makassar, 2024)
This research aims to describe the bill on alcoholic beverages and the criticism of elitism in the song lyrics and music video of Orang Miskin Dilarang Mabok. The approach used in this research is a qualitative approach that is interpretative in nature to describe data analysis related to the main points of discussion in the research. The material object in this research is the song lyrics and visuals of Orang Miskin Dilarang Mabok by Libertaria in collaboration with Sirin Farid Stevy, vocalist of rock music group FSTVLST. The research data was analysed using the qualitative data analysis method of Miles and Huberman. The results of the research show that through a qualitative approach that is descriptive-interpretative as a research method, the meaning of the song lyrics and music video of Orang Miskin Dilarang Mabok has a connection with the discourse of criticism of elitism and irregularities in the issuance of the Alcoholic Beverage Prohibition Bill.